EFFECTIVENESS OF LAW ENFORCEMENT AGAINST TRAFFIC VIOLATIONS COMMITTED BY TEENAGERS (STUDY AT LABUHANBATU POLICE) - Achmad Chayrul Efendi; M. Citra Ramadhan; Azwir Agus (SOSIOEDUKASI, 2026)
Traffic violations committed by juveniles are a legal problem that continues to occur frequently and tends to increase, including in the jurisdiction of the Labuhanbatu Police. This condition not only impacts the safety of road users but also poses challenges in law enforcement, considering that juveniles are legal subjects who are categorized as children and have the right to legal protection. Therefore, law enforcement against traffic violations by juveniles needs to be implemented effectively, proportionally, and oriented towards developmental aspects. The research questions in this study are: 1. How is law enforcement regulated against traffic violations in the Labuhanbatu Police Traffic Unit? 2. How is law enforcement against traffic violations committed by juveniles in the Labuhanbatu Police Traffic Unit? 3. How effective is the Labuhanbatu Police Traffic Unit's response to juvenile traffic violations? The type of research used is normative legal research with a normative juridical approach. This research examines positive legal norms governing road traffic and transportation, specifically Law Number 22 of 2009 concerning Road Traffic and Transportation, as well as other laws and regulations related to law enforcement and child protection. This research is descriptive and analytical in nature, describing applicable legal provisions and analyzing their application systematically, logically, and consistently in traffic law enforcement practices against juveniles.